2007
DOI: 10.1634/stemcells.2007-0238
|View full text |Cite
|
Sign up to set email alerts
|

Selective Targeting of Adenoviral Vectors to Neural Precursor Cells in the Hippocampus of Adult Mice: New Prospects for In Situ Gene Therapy

Abstract: The adult brain contains neural precursor cells (NPC) that are attracted to brain lesions, such as areas of neurodegeneration, ischemia, and cancer. This suggests that NPC engineered to promote lineage-specific differentiation or to express therapeutic genes might become a valuable tool for restorative cell therapy and for targeting therapeutic genes to diseased brain regions. Here we report the identification of NPC-specific ligands from phage display peptide libraries and show their potential to selectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Primary neural stem and progenitor cells (NSPCs) were isolated from the lateral wall of lateral ventricles (SVZ) and hippocampus (HC) of 4-week-old C57/B6 mice (Charles River Lab., USA), expanded, and differentiated under removal of growth factors as previously described (Schmidt et al , 2007. Mice were anaesthetized using ketamine (75 mg/kg) and rompun (5.8 mg/kg) and killed by decapitation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary neural stem and progenitor cells (NSPCs) were isolated from the lateral wall of lateral ventricles (SVZ) and hippocampus (HC) of 4-week-old C57/B6 mice (Charles River Lab., USA), expanded, and differentiated under removal of growth factors as previously described (Schmidt et al , 2007. Mice were anaesthetized using ketamine (75 mg/kg) and rompun (5.8 mg/kg) and killed by decapitation.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the most important challenge is to develop Ad-derived gene delivery systems with high efficiency through target cell selectivity, in particular under in situ conditions (Reetz et al 2014). Our recent endeavors in the generation of Ad vectors that specifically target stem/progenitor cells in the body have focused on linking selective peptides to viral particles that direct the virus to specific or yet unknown receptors on the surface of stem cells (Hildebrandt et al 2010;Schmidt et al 2007). Using an Ad-PEGylation approach, we demonstrated that a short artificial peptide selected by phage display, which specifically binds neural precursor cells derived from the hippocampal area of adult mice or rats, was highly effective in targeting NSPCs after virus administration into the brain (Hildebrandt et al 2010;Schmidt et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, nanomaterials can incorporate peptide ligands to specifically target endogenous NSCs. Some ligands have been identified by phage display peptide libraries [5]. Importantly, functionalized nanostructured hydrogels were shown to successfully induce NSC differentiation while supporting tissue regeneration [6].…”
Section: Modulation Of Endogenous Nscsmentioning
confidence: 99%
“…A similar approach involves the pre-selection of peptides by using a phage display peptide library, from which peptides with high affinity for a certain cell type are selected and then inserted into the AdV vector capsid. This has allowed the targeting of AdV vectors to epithelium cells (Nicklin et al, 2001b), tumor cells (Rittner et al, 2007), and neurons (Schmidt et al, 2007). Most efforts to modify the AdV vector capsid have been on vector targeting to tumor cells (Bachtarzi et al, 2008).…”
Section: Genetic Modification Of the Adv Capsidmentioning
confidence: 99%